Effectiveness and cost-effectiveness of unsupervised buprenorphine-naloxone for the treatment of heroin dependence in a randomized waitlist controlled trial. (1st May 2017) - Dunlop, Adrian J.; Brown, Amanda L.; Oldmeadow, Christopher; Harris, Anthony; Gill, Anthony; Sadler, Craig; Ribbons, Karen; Attia, John; Barker, Daniel; Ghijben, Peter; Hinman, Jennifer; Jackson, Melissa; et al.
Highlights: First cost-effectiveness study comparing buprenorphine-naloxone to a waitlist. Relative to controls, treatment group heroin use was reduced over the study period. Unsupervised dosing is a cost-effective strategy to enhance treatment capacity. Treatment was associated with reductions in crime. Treatment was associated with improvements in quality of life and mental health. Abstract: Background: Access to opioid agonist treatment can be associated with extensive waiting periods with significant health and financial burdens. This study aimed to determine whether patients with heroin dependence dispensed buprenorphine-naloxone weekly have greater reductions in heroin use and related adverse health effects 12-weeks after commencing treatment, compared to waitlist controls and to examine the cost-effectiveness of this strategy. Methods: An open-label waitlist RCT was conducted in an opioid treatment clinic in Newcastle, Australia. Fifty patients with DSM-IV-TR heroin dependence (and no other substance dependence) were recruited. The intervention group (n = 25) received take-home self-administered sublingual buprenorphine-naloxone weekly (mean dose, 22.7 ± 5.7 mg) and weekly clinical review. Waitlist controls (n = 25) received no clinical intervention. The primary outcome was heroin use (self-report, urine toxicology verified) at weeks four, eight and 12. The primary cost-effectiveness outcome was incremental cost per additional heroin-free-day. Results: Outcome data were available for 80% of all randomized participants. Across the 12-weeks, treatment group heroin use was on average 19.02 days less/month (95% CI −22.98, −15.06, p < 0.0001). A total 12-week reduction in adjusted costs including crime of A5, 722 (95% CI 3299, 8154) in favor of treatment was observed. Excluding crime, incremental cost per heroin-free-day gained from treatment was A18.24 (95% CI 4.50, 28.49). Conclusion: When compared to remaining on a waitlist, take-home self-administered buprenorphine-naloxone treatment is associated with significant reductions in heroin use for people with DSM-IV-TR heroin dependence. This cost-effective approach may be an efficient strategy to enhance treatment capacity.